2021
DOI: 10.3389/fvets.2021.743725
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Isolated From Milk of Dairy Cows With and Without Clinical Mastitis in Different Regions of Australia and Their AMR Profiles

Abstract: Mastitis is the most common disease in dairy cattle worldwide. The objectives of this study were to estimate the prevalence of different bacterial species associated with mastitis from dairy herds located in geographically and climatically distinct zones in Australia, and to evaluate the antimicrobial susceptibility of the isolated bacteria. Quarter-level milk samples (n = 419) were collected from 151 mastitis cases and 268 healthy controls originating from 18 dairy herds located in tropical (Northern Queensla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 62 publications
(89 reference statements)
3
17
3
Order By: Relevance
“…None of the isolates were sensitive for all antimicrobials, an aspect also observed by others [ 34 , 35 , 36 ]. In the present research, all 14 strains tested showed the multiple resistance phenomenon, as follows: six strains (42.9%) to five antimicrobials, three strains (21.4%) to six antimicrobials, two strains (14.3%) to eight antimicrobials, two strains (14.3%) to nine antimicrobials and one strain (7.1%) to ten antimicrobials.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…None of the isolates were sensitive for all antimicrobials, an aspect also observed by others [ 34 , 35 , 36 ]. In the present research, all 14 strains tested showed the multiple resistance phenomenon, as follows: six strains (42.9%) to five antimicrobials, three strains (21.4%) to six antimicrobials, two strains (14.3%) to eight antimicrobials, two strains (14.3%) to nine antimicrobials and one strain (7.1%) to ten antimicrobials.…”
Section: Resultssupporting
confidence: 78%
“…The target plate was then loaded on MALDI-TOF Biotyper and identified by comparing the mass spectral protein detection pattern with the reference patterns in database. A score of >0.2 was accepted as representing a reliable identification [ 34 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results obtained in this paper corresponded to Australian studies, in which S. uberis was the most commonly cultivated bacterial species collected from milk samples (Dyson et al, 2022). Al-harbi et al also described S. uberis as the most common species of Streptococcus spp., however, the percentage was fourfold lower compared to our results (Al-harbi et al, 2021). In the European cattle population, S. uberis is also described as the most common agent causing mastitis (Tenhagen et al, 2006;Botrel et al, 2010).…”
Section: Discussioncontrasting
confidence: 84%
“…In most of the clinical cases of mastitis in our study, were caused by Streptococcus spp. The obtained results corresponded to the investigation described by Al-harbi et al (Al-harbi et al, 2021), as well as to the North American cattle population (Schukken et al,TABLE 2 Bioinformatic prediction of proteins' cell localization (Busca database), detection of signal peptides (PRED-LIPO), classical (SignaIP) and nonclassical (Secretome, PncsHub) proteins, and prediction of antigenicity (VaxiJen). 2009; Levison et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…host cell/DNA exists. Most previous research that used PF (Ganda et al, 2016;Lima et al, 2018;Taponen et al, 2019;Al-Harbi et al, 2021;Ma T. et al, 2021;Schwenker et al, 2022) or NG kit (Quigley et al, 2012;Cheema et al, 2021;Lyons et al, 2021) considered 16S metagenomic sequencing for bacterial identification following DNA extraction; therefore, no host DNA contamination was reported. While amplicon sequencing is a sensitive method for taxonomy clarification, the relevance of this approach for rapid diagnostic and AMR gene detection in mastitis is questionable.…”
Section: Food-specific Bacterial Dna Isolation Kits Yielded a Lower N...mentioning
confidence: 99%